At the heart of programming: the role of micro-RNAs. (18th June 2018) - Siddeek, B.; Mauduit, C.; Yzydorczyk, C.; Benahmed, M.; Simeoni, U.
Abstract: Epidemiological and experimental observations tend to prove that environment, lifestyle or nutritional challenges influence heart functions together with genetic factors. Furthermore, when occurring during sensitive windows of heart development, these environmental challenges can induce an 'altered programming' of heart development and shape the future heart disease risk. In the etiology of heart diseases driven by environmental challenges, epigenetics has been highlighted as an underlying mechanism, constituting a bridge between environment and heart health. In particular, micro-RNAs which are involved in each step of heart development and functions seem to play a crucial role in the unfavorable programming of heart diseases. This review describes the latest advances in micro-RNA research in heart diseases driven by early exposure to challenges and discusses the use of micro-RNAs as potential targets in the reversal of the pathophysiology.